Implementasi Program Pelatihan Kerja di Dinas Tenaga Kerja Kabupaten Pelalawan - Dinda Ardiyanti; Abdul Sadad (UIR Press, 2021)
The job training program organized by the Pelalawan Regency Manpower Office is a program that aims to improve the competence of Human Resources in Pelalawan Regency. The Pelalawan Regency Government is committed so that people who participate in this job training program can open their business independently or get a job according to their expertise so that this can reduce unemployment in Pelalawan Regency. The purpose of this study was to knowing the implementation of job training programs and the factors that hinder the successful implementation of job training programs in Pelalawan District. The method in this study uses a descriptive qualitative methode. The theory concept used in this research is Edward III theory, namely 1) communication, 2) resources, 3) disposition, and 4) bureaucratic structure. The results of this study indicate that the implementation of the Pelalawan district job training program has not been said to be optimal, namely from the communication and resource criteria. In its implementation there are still obstacles that occur such as 1) lack of instructors, 2) the absence of a Work Training Center, and 3) limited budget in the implementation of job training.